2013
DOI: 10.1007/s10517-013-2023-6
|View full text |Cite
|
Sign up to set email alerts
|

Coexpression of Two mRNA Isoforms of Insulin-Like Growth Factor-1 Gene and mRNA of YB-1 Gene in Patients with Multiple Myeloma

Abstract: Coexpression of two mRNA isoforms for insulin-like growth factor-1 (IGF-1A and IGF-1B) and expression of YB-1 mRNA were analyzed in the bone marrow aspirates from 19 patients with multiple myeloma. It was shown that mRNA isoforms for IGF-1A and IGF-1B were mainly expressed in samples with hyperexpression of YB-1 mRNA, and, on the contrary, practically were not expressed (except sporadic cases) in samples with low level of YB-1 mRNA expression. Coexpression of mRNA isoforms for IGF-1A and IGF-1B were observed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
1
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
3
1
0
Order By: Relevance
“…Hence, mRNA expression of insulin receptor only A isoform was characteristic of the studied MM cells. These results completely coincided with our previous data indicating the expression of mainly IRA mRNA in clinical samples from MM patients [1].…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Hence, mRNA expression of insulin receptor only A isoform was characteristic of the studied MM cells. These results completely coincided with our previous data indicating the expression of mainly IRA mRNA in clinical samples from MM patients [1].…”
Section: Resultssupporting
confidence: 92%
“…According to some data, stimulation of IRA mediates proliferative effects, while activation of IRB mediates metabolic effects [7,14]. In a previous study [1], we have focused on IRA and IRB mRNA expression in aspirated bone marrow specimens from patients treated for stage III multiple myeloma (MM). These samples express mainly IRA mRNA (in 100% cases), while the expression of IRB mRNA is found in only 32% patients.…”
mentioning
confidence: 99%
“…In the present study, HIF1α and IGF1 mRNA expression levels were significantly increased in RPMI-8226 and primary myeloma cells compared with those in healthy donor cells. The results have confirmed the data of previous studies (3)(4)(5)10,39), which have suggested that high levels of HIF1α and IGF1 contribute to angiogenesis and promote MM disease progression.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, we documented an increased expression of IGF-IEc isoform in secondary compared to primary foci of neuroendocrine neoplasms (18). Other investigators have reported the overexpression of IGF-IEa and IGF-IEb in multiple myeloma patients (41) and of IGF-IEb in uterine cancer (23).…”
Section: Discussionsupporting
confidence: 71%